Tantangan Kompetensi Kognitif pada Mata Pelajaran Pendidikan Agama Islam di Sekolah Menengah Atas Alfa Centauri Bandung - Asep asep Mulyana; Chaerul Rochman; Agus Salim (Institut Studi Islam Muhammadiyah (ISIMU) Pacitan, 2019)
This study was conducted to identify the cognitive abilities in the evaluation of Islamic religious education learning at Alfa Centauri Senior High School in Bandung based of the level of hardness of questions based on Hots (Higher Order of Thinking Skill questions. This research method uses descriptive participation method. The population is a whole class which consists of nine classes. From the nine classes, taken one class as sample, it is 11 with total number of students 22, which determination of the sample using cluster random sampling technique. The techniques of collection data was taken by test about muamalah material., interviews, observation, and documentation. The instrument used refers to essay test which refers to the Hots question. The conclusions of this study are (1) the achievement profile of the students' cognitive abilities, showed varying results with an average achievement of 80.4%, Cognitive abilities of students at level C1 which is equal to 96.25% belong to category “very good”, at level C2 which is equal to 91.25% included in the very “good category” too, at the C3 level of 73.75% included in the category “enough”, at C4 level of 82.5% included in the category “good”, at the level C5 which is equal to 91.25% included in the category “very good” and the last at the Level C6 which is equal 54.0% included in the category “low”. Recommendations for the results of this study for students It is expected that students can understand more in the important sense of learning Islamic education and for teachers are expected to be able to give more attention and use interesting methods to increase the enthusiasm of students in learning Keywords: Competence, cognitive, Islamic Education, senior hight School.